2016
DOI: 10.1074/jbc.m116.741835
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Conserved Residues of the Glycine Oxidase GoxA in Controlling Activity, Cooperativity, Subunit Composition, and Cysteine Tryptophylquinone Biosynthesis

Abstract: GoxA is a glycine oxidase that possesses a cysteine tryptophylquinone (CTQ) cofactor that is formed by posttranslational modifications that are catalyzed by a modifying enzyme GoxB. It is the second known tryptophylquinone enzyme to function as an oxidase, the other being the lysine ϵ-oxidase, LodA. All other enzymes containing CTQ or tryptophan tryptophylquinone (TTQ) cofactors are dehydrogenases. Kinetic analysis of GoxA revealed allosteric cooperativity for its glycine substrate, but not O This is the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Those characterized to date catalyze the oxidative deamination of the ε-amino group of lysine (LodA) or the amine group of glycine (GoxA). Some features of the reductive half-reaction are similar to those of MADH, AADH and QHNDH, but some are different 18,19 . The LodA-like proteins are oxidases, using molecular oxygen as an electron acceptor 18 .…”
Section: Introductionmentioning
confidence: 91%
“…Those characterized to date catalyze the oxidative deamination of the ε-amino group of lysine (LodA) or the amine group of glycine (GoxA). Some features of the reductive half-reaction are similar to those of MADH, AADH and QHNDH, but some are different 18,19 . The LodA-like proteins are oxidases, using molecular oxygen as an electron acceptor 18 .…”
Section: Introductionmentioning
confidence: 91%
“…L AAO (L-amino acid oxidase) is an amino acid-metabolizing enzyme that catalyzes the oxidation of the main-chain amino group of L-amino acids, thereby generating ␣-keto acid and ammonia (1). Two types of LAAOs have been reported: one is flavin adenine dinucleotide (FAD) dependent (2)(3)(4) while the other is not FAD dependent (5)(6)(7)(8). The former type of LAAO is the main target of this study.…”
mentioning
confidence: 99%
“…Previous studies of tryptophylquinone-bearing enzymes have shown that mutation of active site residues is not well-tolerated. Mutation of the active site Asp residue that corresponds to Asp-678 in the TTQ-dependent methylamine dehydrogenase (16) and the CTQ-dependent MmLodA (14) and MmGoxA (12) prevented the formation of the quinone cofactor. Mutation of some other active site residues in these enzymes also prevented or reduced the levels of cofactor biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The inter-subunit projection of these residues suggests a role in cooperativity. It was previously shown that Phe-237 in MmGoxA plays a role in its cooperative kinetic behavior (12). The corresponding residue in PlGoxA is Phe-316, which suggests that it may also play a role in cooperativity of PlGoxA.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation